2019
DOI: 10.1002/phar.2237
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Sofosbuvir‐Based Therapy on Liver Transplant Candidates with Hepatitis C Virus Infection

Abstract: BACKGROUND Sofosbuvir use in patients with decompensated cirrhosis may be associated with reduced liver transplant waitlist mortality and reduced need for transplant. METHODS Data from the Scientific Registry of Transplant Recipients were linked with a national database of pharmacy claims. All adult patients on the liver transplant waitlist on January 1, 2014, or added to the list during 2014, with hepatitis C virus as reason for listing were identified (2009 patients). A subgroup of 1093 unique patients had c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…Of 5691 articles initially identi ed, 51 full articles were reviewed for eligibility, but only 8 10,12,[21][22][23][24][25][26] met the criteria and were included in systematic review (Fig. 1).…”
Section: Search Results and Study Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations
“…Of 5691 articles initially identi ed, 51 full articles were reviewed for eligibility, but only 8 10,12,[21][22][23][24][25][26] met the criteria and were included in systematic review (Fig. 1).…”
Section: Search Results and Study Characteristicsmentioning
confidence: 99%
“…1). Among them, ve 10,12,23,24,26 , four 10,12,25,26 and three 12,21,22 studies reported overall survival, HCC occurrence, and MELD score, respectively. Characteristics of included studies are described in Table 1.…”
Section: Search Results and Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, only 8 studies met the inclusion criteria ( 10 , 13 , 22 27 ) and were included in the systematic review ( Figure 1 ). Among them, five studies reported OS ( 10 , 13 , 24 , 25 , 27 ) four studies reported HCC occurrence ( 10 , 13 , 26 , 27 ) and three reported MELD scores ( 13 , 22 , 23 ). The characteristics of the included studies are summarized in Table 2 .…”
Section: Resultsmentioning
confidence: 99%